(untitled) (International Journal of Engineering and Computer Science, 2014)
WiMAXtechnology is a new trend in wireless communication. The IEEE Standard 802.16 WiMAX protocol provides wireless broadband access to homes, businesses and core telecommunication networks worldwide. Many sophisticated authentication and encryption techniques have been embedded into WiMAX but it still exposes to various attacks in. This paper provides a mechanism for increasing the efficiency and hence improves the existing model of 802.16 protocols using new public key algorithm. We are attempting here new algorithm based on block cipher (Nlbc) for the replacement of RSA algorithm which is using in the IEEE Standard 802.16 WiMAX Technology.